2014
DOI: 10.1021/jo5025317
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic C–H Allylation and Benzylation of Pyrazoles

Abstract: We describe a general approach for the synthesis of allylated and benzylated pyrazoles. An electron-withdrawing substituent, such as nitro, chloro, and ester groups, at C4 renders the Lewis basic nitrogen atom to be less basic and the C-H bond more acidic than the ones of the parent ring, enabling Pd-catalyzed C-H allylation and benzylation reactions of pyrazoles. The new method expanding the scope of the C-H functionalization of pyrazoles beyond arylation reactions provides a rapid access to complex pyrazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 68 publications
3
16
0
1
Order By: Relevance
“…A competition experiment with substituted oxadiazoles was also performed (Scheme 3 b). The formation of 3 c and 3 j in a 2:3 ratio suggested that the oxadiazole bearing an electron withdrawing substituent reacts preferably with the 1,4‐Pd‐migration intermediate D , which could be accounted for preferential deprotonation as compared to electron‐rich 3 c [20] …”
Section: Methodsmentioning
confidence: 99%
“…A competition experiment with substituted oxadiazoles was also performed (Scheme 3 b). The formation of 3 c and 3 j in a 2:3 ratio suggested that the oxadiazole bearing an electron withdrawing substituent reacts preferably with the 1,4‐Pd‐migration intermediate D , which could be accounted for preferential deprotonation as compared to electron‐rich 3 c [20] …”
Section: Methodsmentioning
confidence: 99%
“…The introduction of an electron-withdrawing group on C4 of the pyrazole allowed the direct CH regioselective allylation at C5, thanks to the increased CH acidity with respect to the nitrogen ring. 2 In 2016, a similar strategy was applied to a palladium-catalyzed C2 allylation of indoles 1 using allylic acetates 2, followed by cyclization. 3 The electronic properties of the indole ring were modulated with different substituents, where R 1 = Cl was the most effective (Scheme 2).…”
Section: -Allylpalladium Complexes Generated From Allyl Electrophilementioning
confidence: 99%
“…一种高效的通过双 C-H 活化直接氧化环化得到苯 并呋喃[3,2-b]吡啶氧化物类化合物的方法已经报道 [42] , 所生成的产物在 Pd/C 催化下脱氧生成相应的苯并呋喃 Self-cyclization reaction mechanism of 2-phenoxypyridine 等 [43] 与上述反应类似, 取代 1-苯基吡唑可以与活性较差 的氯苄发生芳杂环上的 C-H 活化芳基化反应 [49] . 位于 吡唑 C(4)的吸电子基团(如硝基、氯和酯基), 呈现出路 易斯碱性使得吡唑环比其他环 C-H 具有更强的酸性, 从而更易于发生 C(5)苄基化(Eq.…”
Section: -苯氧基吡啶也可以与芳基三氟硼酸钾发生邻位unclassified